2013
DOI: 10.1177/0956797612450891
|View full text |Cite
|
Sign up to set email alerts
|

The Good Life of the Powerful

Abstract: A common cliché and system-justifying stereotype is that power leads to misery and self-alienation. Drawing on the power and authenticity literatures, however, we predicted the opposite relationship. Because power increases the correspondence between internal states and behavior, we hypothesized that power enhances subjective well-being (SWB) by leading people to feel more authentic. Across four surveys representing markedly different primary social roles (general, work, romantic-relationship, and friendship s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
89
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 232 publications
(103 citation statements)
references
References 38 publications
11
89
2
1
Order By: Relevance
“…The results showed that both power and authenticity negatively predicted well-being (see Table 2). These results imply that increases in the levels of power and authenticity may be linked to lower well-being which contradicts findings of Kifer et al (2013) on the hypothesized benefits of power on optimal psychological outcomes. Furthermore, the findings revealed that authenticity mediated the relations between power and subjective well-being since the negative but significant predictive impact of power on well-being (Β = -.11, p < .05) was no longer significant (Β = -.09, p = .18) after controlling the effects of authenticity.…”
Section: Power and Happiness In The Asian Contextcontrasting
confidence: 77%
See 4 more Smart Citations
“…The results showed that both power and authenticity negatively predicted well-being (see Table 2). These results imply that increases in the levels of power and authenticity may be linked to lower well-being which contradicts findings of Kifer et al (2013) on the hypothesized benefits of power on optimal psychological outcomes. Furthermore, the findings revealed that authenticity mediated the relations between power and subjective well-being since the negative but significant predictive impact of power on well-being (Β = -.11, p < .05) was no longer significant (Β = -.09, p = .18) after controlling the effects of authenticity.…”
Section: Power and Happiness In The Asian Contextcontrasting
confidence: 77%
“…As power was associated with success (Anderson et al, 2012), previous empirical studies have explored the beneficial consequences of power on the psychological functioning of individuals. Power positively predicted emotional well-being (Adler, Epel, Castellazzo, & Ickovics, 2000), selfesteem (Adler et al, 2000), and life satisfaction (Kifer et al, 2013). These evidences clearly suggest that power may potentially enhance well-being.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations